Business process improvement and the knowledge flows that cross a private online social network: An insurance supply chain case. Issue 4 (July 2020) - Leon, Ramona-Diana; Rodríguez-Rodríguez, Raúl; Gómez-Gasquet, Pedro; Mula, Josefa
Highlights: It analyzes the knowledge shared by employees and suppliers within an enterprise social network. Internal and external social networks have a different and powerful impact on process improvement. Internal and external social networks influence the average cycle time of handling claims. Not all the characteristics of the social network influence process improvement. Abstract: This paper analyses how the knowledge shared between employees and suppliers within a private enterprise social network affects process improvement. Data was collected from internal documents, and the internal and external enterprise social networks used by an international insurance company; the average cycle time for handling 8494 claims and 3240 messages posted on the internal and external social networks was analysed. Social network analysis techniques were combined with principal component analysis and structural equation modeling, and the results demonstrate that the knowledge shared within the internal and external social network can explain 35.10% of process improvement variability, while the knowledge shared within the internal social network explains 89.90% of external social network variability. The analysis also demonstrates that: (i) the knowledge shared among employees positively affects process improvement; (ii) the knowledge shared among suppliers negatively affects process improvement; and (iii) the knowledge shared among employees positively affects the knowledge shared among supply chain members. These findings have theoretical and practical implications. They extend the literature in the knowledge management and information management field by offering empirical evidence of how the knowledge shared through an enterprise social network affects business process improvement, using the objective data provided by Yammer. They also provide a strategic tool for managers that will allow them to better understand how they can use the enterprise social network for business processes improvement.